Mandibular velocities in bruxists - Faulkner Keith D.B (Sciendo, 1998)
Bruxism is a condition of interest to orthodontists because of implications relating it to occlusion. Quantitative analysis of the velocities of a point in the midline of the mandible revealed significant difference in opening and closing during chewing, but provided no information from the tooth tapping task. Because bruxism can be difficult to detect in some patients, these results indicate that further investigation and development of the technique of the analysis of jaw movements might be useful as a diagnostic tool. They also point to the value of further study into the possibility of detecting 'potential' bruxists thus allowing preventive programs for bruxism to be developed.